Current issues in European migration - Thomas Straubhaar; Achim Wolter (Intereconomics, 1996)
The pattern of migration into the EU and within the EU has changed greatly in recent years. Does this make it necessary to introduce a common European migration policy? How is the planned eastern enlargement of the EU to be seen against this background?
Keywords: 330; EU